2015
DOI: 10.1111/1467-8268.12136
|View full text |Cite
|
Sign up to set email alerts
|

Aid, Employment and Poverty Reduction in Africa

Abstract: Growth in Africa is weakly linked to poverty reduction. The reason is that Africa has failed to create enough good jobs. Structural transformation-the relative growth of employment in high productivity sectors-has not featured in Africa's post-1995 growth story. As a result, the region's fastest growing economies have the least responsiveness of employment and poverty to growth. Development aid is partly responsible. Across Africa more aid went to countries with a low employment intensity of growth. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…Azam (2014) finds that foreign aid has significantly negative impact on economic growth of in Pakistan during 1972-2012. More recently, Page and Shimeles (2014) observed that the role of development aid in across Africa is problematic, where huge aid went to countries with a little employment intensity of growth.…”
Section: Prior Empirical Studiesmentioning
confidence: 99%
“…Azam (2014) finds that foreign aid has significantly negative impact on economic growth of in Pakistan during 1972-2012. More recently, Page and Shimeles (2014) observed that the role of development aid in across Africa is problematic, where huge aid went to countries with a little employment intensity of growth.…”
Section: Prior Empirical Studiesmentioning
confidence: 99%
“…Yet recent evidence suggests that the continent is anything but hopeless. The share of the population living on less than $1.25 a day fell from 58 percent in 2000 to 48 percent in 2010, infant mortality rates declined significantly, and access to education generally improved (Page and Shimeles, 2014). Average growth rates have been positive for the first time in decades and, in some of the fastest growing economies, have exceeded 6 percent per annum; moreover, these growth rates are likely to be underestimated.…”
mentioning
confidence: 99%
“…Previous researchers have shown that agriculture is by far the least productive sector in Africa (McMillan and Rodrik (2011) and Gollin, Lagakos and Waugh (2014)) and that income and consumption are lower in agriculture than in any other sector (McMillan and Verduzco (2012) and Gollin, Lagakos and Waugh (2014)). Researchers have also noted that real consumption is growing in Africa (Young (2012)) and that poverty is falling (Shimeles and Page (2014)). To our knowledge, this paper is the first to connect these improvements in living standards to important occupational changes.…”
mentioning
confidence: 99%
“…Recent research suggests that most of the recent growth seen in many African countries is mainly a result of booming commodity prices and a favorable international investment climate, particularly in the extractive industry sectors [8], [9]. However, the intensity of employment generated during this period of rapid growth has been very low [10]. This is primarily because there has been very little improvement in the production and employment structure of African economies.…”
Section: Shifting Focus From Primary To Higher Educationmentioning
confidence: 99%